Evaluation of the virulence of entomopathogenic fungus, Isaria fumosorosea isolates against subterranean termites Coptotermes spp. (Isoptera: Rhinotermitidae) - J. J., Jessica; Peng, T. L.; Sajap, A. S.; Lee, S. H.; S. A., Syazwan (Springer, 2019)
The entomopathogenic fungus Isaria fumosorosea Wize, formerly known as Paecilomyces fumosoroseus is reported as a promising biocontrol agent for controlling subterranean termites, particularly those belonging to the family Rhinotermitidae. In Malaysia, the family Rhinotermitidae includes two species of subterranean termites with extremely high economic importance; namely Coptotermes curvignathus Holmgren, and the Asian Subterranean Termite (Coptotermes gestroi Wasmann). To comprehend the potential control of this soil-dwelling fungus against these subterranean termites in Malaysia, an investigation was carried out by testing the pathogenecity of 11 isolates against these termite species. All isolates showed pathogenic potential against the termite (Mortality rate of C. curvignathus: 84.4%; C. gestroi: 67.3%). Isolate PF49 was the most effective against both species of termites and was further tested for its virulence and mycosis. The LC50 values of PF49 against C. curvignathus and C. gestroi were 7.55 × 103 and 1.09 × 102 conidia/ml, respectively. The average number of days required to complete the mycosis process in C. curvignathus and C. gestroi were 4.7 and 8 days, respectively. These fungi are believed useful for protecting living trees, plants, wood, wood structures, and other cellulosic materials susceptible to termite infestation and damage.